Analisis Pengaruh Kepercayaan dan Pengalaman Pelanggan Terhadap Loyalitas Pelanggan Pengguna Jasa Pengangkutan PT. Truk Toto - Revaldo; Kevin; Marco; Jeff; Jehan (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the influence of trust and customer experience on customer loyalty in freight services, with a case study at PT. Truk Toto. Since the population size is unknown, the sample was determined using Hair’s formula, involving 120 respondents selected through direct questionnaire distribution. The data were analyzed using multiple linear regression to assess both partial and simultaneous effects. The results show that trust and customer experience have a positive and significant effect on customer loyalty, as proven by t-tests and F-tests with significance values below 0.05. Among the two variables, customer experience has a greater influence on loyalty. The coefficient of determination (R²) is 0.717, indicating that 71.7% of the variation in customer loyalty is explained by trust and customer experience. These findings suggest that trust and experience are key factors in building long-term loyalty in the logistics sector. PT. Truk Toto is advised to continuously improve the quality of customer experience and maintain customer trust to enhance retention and strengthen competitive advantage.